2008
DOI: 10.1099/mic.0.2008/018630-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous presence of two different copies of the 16S rRNA gene in Bartonella henselae

Abstract: Bartonella henselae is an emerging pathogen of increasing medical significance. Previous investigations have revealed two different 16S rRNA gene variants among B. henselae isolates, resulting in delineation of the B. henselae population into 16S RNA type I and type II isolates. While studying 191 B. henselae isolates by multi-locus sequence typing (MLST) we detected three isolates that could not be assigned to a distinct 16S RNA type upon direct sequencing because of ambiguous nucleotides in a distinct region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The gene is located in a genomic locus, where the upstream side is a group of four ORFs ending with the hisS (histidyl-tRNA synthetase) gene. The downstream side of gpsA in lineage 2 Bartonella genomes is an rRNA operon, which is typically present in all Bartonella genomes as two to three copies (Viezens and Arvand 2008; Guy et al 2013). The horizontal transfer of gpsA (He) into lineages 1 and 2 seems to have interrupted an ORF present in all bartonellae, which in lineage 2 bartonellae is still present with a residual sequence (fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gene is located in a genomic locus, where the upstream side is a group of four ORFs ending with the hisS (histidyl-tRNA synthetase) gene. The downstream side of gpsA in lineage 2 Bartonella genomes is an rRNA operon, which is typically present in all Bartonella genomes as two to three copies (Viezens and Arvand 2008; Guy et al 2013). The horizontal transfer of gpsA (He) into lineages 1 and 2 seems to have interrupted an ORF present in all bartonellae, which in lineage 2 bartonellae is still present with a residual sequence (fig.…”
Section: Resultsmentioning
confidence: 99%
“…These authors concluded that human isolates come from a limited subset of B. henselae strains. More recent analysis using multi-locus sequence typing (MLST) [5, 68, 87, 132] or multiple-locus variable-number tandem-repeat analysis (MLVA) also support the wide diversity of feline strains and the clustering of human cases within the broad range of feline isolates [17, 98]. A small percentage of B. henselae isolates may harbor two different 16S rRNA gene copies and these isolates may have emerged by horizontal gene transfer [132].…”
Section: Adaptation Of Bartonella Species To the Mammalian Hostmentioning
confidence: 99%
“…An examination of polymorphisms in spacer regions showed similar levels of genetic diversity of the human and feline B. henselae strains [21], with some evidence for a history of recombination [18]. This was substantiated by the finding of hybrid 16S rRNA alleles in a small fraction (< 2%) of the population [22]. The rRNA genes are located inside the amplified region of the chromosome and the increased copy number of these genes could potentially increase their propensity for recombination [16].…”
Section: Introductionmentioning
confidence: 99%